Effects of mindfulness training on anxiety, stress resilience, and self-confidence in wushu taolu athletes - Xu Shuai; Sapto Wibowo; Heryanto Nur Muhammad (Universitas Nusantara PGRI Kediri, 2026)
Wushu taolu requires not only physical skill and technical precision but also strong mental stability to perform under pressure. However, many athletes struggle with high levels of anxiety, competitive stress, and diminished self-esteem, factors that significantly undermine their performance. These persistent psychological challenges make it essential to implement mindfulness as a targeted mental intervention, enabling athletes to regulate their emotions, sustain focus, and maintain composure throughout competition. This study examined the effects of mindfulness training on anxiety, stress resilience, and self-confidence among wushu taolu athletes. A quasi-experimental design with a non-equivalent control group pretest–posttest was used. Participants were 33 athletes from the East Java Wushu Team: 17 participated in a four-week mindfulness program (three sessions per week, 30–40 minutes), while 16 continued their normal training. Standardized scales measured psychological changes before and after treatment. Results showed the mindfulness group had lower cognitive (ΔM = 4.76; p < 0.001) and somatic anxiety (ΔM = 4.35; p < 0.001), and higher resilience (ΔM = 4.82; p < 0.001) and confidence (ΔM = 5.12; p < 0.001). The large effect sizes confirm the intervention's strong impact. In conclusion, mindfulness effectively enhances athletes' psychological readiness for competition. It can be integrated into regular training programs as a practical strategy to strengthen emotional control, focus, and overall psychological performance.